Chronic Invasive Pulmonary Aspergillosis in Two Cats with Diabetes Mellitus. Issue 2 (August 2016) - Leite-Filho, R.V.; Fredo, G.; Lupion, C.G.; Spanamberg, A.; Carvalho, G.; Ferreiro, L.; Driemeier, D.; Pavarini, S.P.; Sonne, L.
Summary: Human patients with diabetes mellitus are at increased risk of fungal infections. Diabetes mellitus has also been implicated as a predisposing factor in the establishment of fungal lung infections in cats. Two diabetic cats of different origins presented with severe acute respiratory conditions that resulted in their death. At necropsy examination there was friable, black material in the main bronchi that obstructed the bronchial lumina. Microscopical examination of the lungs revealed the presence of pneumonia, calcium oxalate crystals and a large quantity of fungal hyphae and conidial heads. Fungal infection was confirmed with Grocott's methenamine silver stain. The results of the mycology analysis were compatible with Aspergillus section Nigri .